Remote Ischemic Conditioning for Intracerebral Hemorrhage (RICH-1): Rationale and Study Protocol for a Pilot Open-Label Randomized Controlled Trial - Zhao, Wenbo; Jiang, Fang; Li, Sijie; Wu, Chuanjie; Gu, Fei; Zhang, Quanzhong; Gao, Xinjing; Gao, Zongen; Song, Haiqing; Wang, Yuping; Ji, Xunming; , the RICH-1 Investigators (Frontiers in Neurology, 2020)
Background and rationale: Although many therapies have been investigated for intracerebral hemorrhage (ICH), none have succeeded in improving the functional outcomes. Remote ischemic conditioning (RIC) has been proven to promote hematoma resolution and improve neurological outcomes in an ICH model; whether it is safe and feasible in patients with ICH remains unknown. This trial aims to assess the safety, feasibility, and preliminary efficacy of RIC in patients with ICH and to plan for a phase-2 study. Methods: A proof-of-concept, assessor-blinded, pilot open-label randomized controlled trial will be carried out with patients with ICH within 24–48 h of ictus. All participants will be randomly allocated to the intervention group and the control group with a 1:1 ratio (n = 20) and will be treated with standard managements according to the guidelines. Participants allocated to the intervention group will receive RIC once daily for 7 consecutive days. Cranial computed tomography examinations will be performed at baseline, and on days 3, 7, and 14. Neurological outcomes will be assessed at baseline, and on days 1 to 14, 30, and 90. The primary outcome to be tested is safety. Secondary tested outcomes include changes of hematoma and perihematomal edema volume, incidence of hematoma expansion, functional outcomes, and frequency of adverse events. Discussions: This study will be the first proof-of-concept randomized controlled trial to ascertain the safety, feasibility, and preliminary efficacy of RIC in patients with ICH, results of which will provide parameters for future studies and provide insights into the treatment of ICH. Trial Registration:Clinicaltrials.gov, identifier: NCT03930940.